Improvement of Realistic Mathematics Learning Outcomes with the Application of Snowball Throwing Learning Model for Students with Intellectual Disability in the Grade VIII of SMPLB - Desy Setyorini; Sudarsini Sudarsini (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
An intellectual disability is a condition in which intelligence is below average. If it is used a conventional learning in the mathematic lesson, it make the students with intellectual disability difficult in understanding. The purpose of this study was to describe the learning outcome in mathematics. The design of this study was Class Action Research (PTK) with two cycles. The subject of the study was five students of eighth grade in SMPLB Negeri Kedungkandang. The results showed that in the first cycle the average score increased to 62.51 %. In the second cycle, the students’ average score was 87,19%. The conclusion is by using snowball throwing model, there was an increase of learning outcomes on pre-action, the first cycle and the second cycleTunagrahita merupakan suatu kondisi di mana intelegensinya berada di bawah rata-rata. Jika pembelajaran matematika dengan menggunakan pembelajaran konvensional, maka akan membuat siswa tunagrahita kesulitan dalam memahaminya. Tujuan penelitian ini adalah mendeskripsikan peningkatan hasil belajar pada mata pelajaran matematika. Penelitian ini menggunakan desain PTK. Dilaksanakan dengan dua siklus. Subyek penelitiannya adalah 5 siswa kelas VIII di SMPLB Negeri Kedungkandang. Hasil penelitian menunjukkan bahwa pada siklus I mengalami peningkatan rata-rata nilai siswa 62,51% dan pada siklus II nilai rata-rata siswa mencapai 87,19%. Kesimpulannya yaitu dengan menggunakan model pembelajaran snowball throwing, terjadi peningkatan hasil belajar antara pratindakan, siklus I, dan siklus II.